Non-Descent Vaginal Hysterectomy - Analysis of 100 Cases - Bandyopadhyay, Soma; Pal, Manidip (Asian Journal of Medical Sciences, 2013)
OBJECTIVE: To evaluate the feasibility of performing vaginal hysterectomy for non-prolapsed uteri as primary route METHODS: 100 patients planned for hysterectomy for a wide range of indications like large uterus, cervix flushed with vagina, previous pelvic surgery were chosen for vaginal hysterectomy. Prerequisite were uterine size not more than 16 weeks, adequate vaginal access and good uterine mobility. Patients with utero-vaginal prolapse, complex adnexal mass and suspected malignancy were excluded. RESULTS: Majority were aged 35 – 45 years (77%) with 8 nullipara and 21 primipara. Commonest indication was fibroid (54%) and largest uterine size was 16 weeks. There were 79 patients with history of different pelvic surgeries. Different morcellation techniques were used in more than 10 weeks sized uteri. Adnexal surgeries were performed in 12 cases without difficulty. In uncomplicated cases average blood loss was 200 ml and operating time was 50 minutes. Most of the patients were discharged by 5th post operative day. Two patients were converted to abdominal route due to bladder injury and slippage of upper pedicle respectively. CONCLUSION: Experience and training can lead gynecologist to consider the vaginal approach as the standard route for hysterectomy. DOI: http://dx.doi.org/10.3126/ajms.v3i1.4471 Asian Journal of Medical Sciences 3(2012) 1-5